Chemical Characteristics of Pumpkin Seed Tempeh from Soybean and Pumpkin Seeds - Pujilestari, Shanti; Sandrasari, Diny A.; Marida, Rimmaria (Bina Nusantara University, 2017)
The aim of this research was to find the effect of the combination of soybean and pumpkin seeds on the chemical characteristics of pumpkin seed tempeh. The pumpkin seed tempeh samples were analyzed for its water, ash, protein, fat, carbohydrate and crude fiber. Meanwhile, support data were isoflavone and zinc. Sensory hedonic was conducted by 25 untrained panelists for selecting the best formulation of soybean and pumpkin seeds in tempeh. The result shows the formulation of soybean and pumpkin seeds in various combinations (100:0, 85:15, 70:30, 55:45, and 40:60). It gives a significant effect on the water, protein, fat, carbohydrate, and crude fiber. Moreover, all acceptance on pumpkin seed tempeh is on the level of ? = 0,01 and ? = 0,05. The best combination of soybean and pumpkin seeds is 40:60, with chemical analysis results which are water (33,7%), ash (5,31%), protein (65,65%), fat (54,57%), carbohydrate (5,94%), crude fiber (14,06%) (db), zinc (30,05 ppm), and isoflavones (42,10 mg/100g). Chemical characteristics of the selective pumpkin seed tempeh have fulfilled SNI 3144-2015 regarding water, protein and fat.